Testing an eHealth model to reduce unexpected cardiovascular events and depress episodes in type-2 diabetes patients of peri-urban areas of Lima city - Nieto Chaupis, Huber (2016)
In this paper, a scheme of teleconsult aimed to improve of type-2 diabetes treatment of patients belonging to Peri-urban at Lima city was designed and tested. In essence, the system measures glucose values and number of depressive episodes continuously. It turns out to be advantageous in the sense that the system would make predictions for next weeks, and thus gives capabilities to health specialists to carry out precise interventions. For instance, when one anomalous event is identified in the sense that the glucose value is above 350 mg/dL and having at least one widely depressive state per week, the health specialist would take rapid decision based on an aggressive program of teleconsults which might be of order of up to 5 per week. In this manner, the recovery of patient to reach stable values might take up to 15 days, after of applying the Telemedicine system. This result can be superimposed to the measured pressure blood values by which it is possible to predict within certain errors, the probability of risk for getting a cardiovascular attack. The present scheme might to reduce the probability of getting a cardiovascular assault by a 25% ± 5% in those patients following the proposed teleconsult system of this study.